2021
DOI: 10.1016/j.cegh.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus disease-19 (COVID-19) lockdown on physical activity and energy expenditure among physiotherapy professionals and students using web-based open E-survey sent through WhatsApp, Facebook and Instagram messengers

Abstract: Background Coronavirus disease - 19 (COVID-19) spread throughout the world and become pandemic. To stop and control the rapid infection of COVID-19 lockdown is the best option. Sudden lockdown implies change in entire lifestyle of the population. Social isolation affects individual's lives by greater reduction in their physical activity, which might increase the chance of infection by reducing immunity. To what extent, the physical activity is reduced during this lockdown period among physiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
3
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 33 publications
(38 reference statements)
11
106
3
13
Order By: Relevance
“…As stated previously by others, PA was significantly influenced by COVID-19 pandemic associated lockdown measures [14][15][16][17][18]. The multidisciplinary, multimodal, and telemedicine-based KTx360 • program approach might have led to the observed stabilization and even an increase in PA in the KTx360 • participants during the lockdown.…”
Section: Discussionsupporting
confidence: 50%
“…As stated previously by others, PA was significantly influenced by COVID-19 pandemic associated lockdown measures [14][15][16][17][18]. The multidisciplinary, multimodal, and telemedicine-based KTx360 • program approach might have led to the observed stabilization and even an increase in PA in the KTx360 • participants during the lockdown.…”
Section: Discussionsupporting
confidence: 50%
“…The reliability and validity of IPAQ-SF have been verified under different backgrounds in different countries [ 27 ], and it has been used to estimate the PA level of adolescents [ 28 ]. A recent study has used the IPAQ-SF to estimate the indoor PA levels in physiotherapy professionals and students during the COVID-19 pandemic [ 29 ]. The IPAQ-SF required the participants to recall the number of days they performed each activity (frequency) and the length of time (duration) they were involved in each daily activity in the last 7 days, as well as the average time spent on sedentary behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, maintaining or increasing physical activity levels have previously been shown to be a successful strategy to mitigate reductions in physical and mental health [ 8 , 9 ]. Therefore, it is worrying that a large number of studies have reported reduced physical activity levels and increased sedentary behaviour in university students during the first 2–4 months of the pandemic [ 7 , 10 , 11 , 12 , 13 , 14 , 15 ]. Indeed, during the initial phases of the pandemic, several studies indicated that university students who had reduced levels of physical activity tended to have worse mental health [ 11 , 16 , 17 ], whereas those who maintained or increased their levels of physical activity had better mental health [ 3 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%